Analysis of Generation Y’s Perceptions on Leadership Factors Affecting Retention in the Beverage Industry - Ramakrishnan, S.; Maran, K. (Prabandhan: Indian Journal of Management, 2016)
This paper examined the Gen Y’s perception on leadership factors, which affected the retention of Gen Y in the beverage industry. A structured questionnaire was used for data collection. Gen Y employees were asked to respond to their perception on retention strategy in their industry focusing on leadership factors with reference to expectation level, present level, and satisfaction level. The data collected were analyzed using statistical tools and exhibited the gaps to improve the retention strategies.